Octoploid blueberry development for drought tolerance: A combined approach of in vitro polyploidization and somatic organogenesis - Alejandra Araujo Heraldez; Susana Valdez Peñuelas; Gabriela Jarpa-Tauler; Aparna Banerjee; Kattia Núñez-Montero; Patricio Arce-Johnson; Jesús L. Romero-Romero (Electronic Journal of Biotechnology)
Background: The blueberry (Vaccinium spp.) is a fruit commercially known for its high quality and health benefits, particularly for its bioactive antioxidant compounds, which are important in the medical field. However, factors such as genotype, stage of fruit ripening and environmental conditions impact the biosynthesis of bioactive compounds in the berry, as well as their yield and cultivation costs. In Mexico, particularly in the state of Sinaloa, extreme climatic conditions limit the cultivation of blueberry and highlight the need for the development of new varieties with low chilling requirements and tolerance to drought conditions. Results: Through the combined use of somatic organogenesis and in vitro polyploidization, genetic variability was promoted in the commercial blueberry plant variety “Biloxi”. To achieve this purpose, blueberry microcuttings were treated with colchicine (0.02%) for six hours for 2, 4, 6 and 8 consecutive days and induced to form shoots in vitro with Zeatin (1 mg·L−1). Out of 304 generated plants, 36 showed lower stomatal density and 9 lines showed higher stomatal density. Likewise, 5 and 49 lines presented lower and larger stomatal sizes, respectively. In 9 lines, a higher chlorophyll content was found (10% to 200%) compared to the control treatment. Ploidy analysis using flow cytometry showed the successful generation of four octoploid blueberry plants. Conclusions: This work successfully generated new octoploid blueberry plants. Currently, all the lines that presented histological, biochemical and/or genetic modifications are being evaluated under greenhouse conditions for fruit quality and drought tolerance.How to cite: Heraldez AA, Peñuelas SV, Jarpa-Tauler G, et al. Octoploid blueberry development for drought tolerance: A combined approach of in vitro polyploidization and somatic organogenesis. Electron J Biotechnol 2025;75. https://doi.org/10.1016/j.ejbt.2025.01.004.